The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00213-006-0480-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol and repetition at encoding on implicit and explicit false memories

Abstract: Article (Unspecified) http://sro.sussex.ac.uk Garfinkel, S.N., Dienes, Zoltán and Duka, Theodora (2006) The effect of alcohol and repetition at encoding on implicit and explicit false memories. Psychopharmacology, 188 (4). pp. [498][499][500][501][502][503][504][505][506][507][508] This version is available from Sussex Research Online: http://sro.sussex.ac.uk/13733/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 44 publications
(74 reference statements)
4
29
1
Order By: Relevance
“…We found that alcohol intoxication did not interfere with this mode of implicit memory processing for neutral and emotional picture cues. Although this lack of a main alcohol effect was consistent with the previous literature that used emotionally neutral word cues (Garfi nkel et al, 2006;Lister et al, 1991;Ray and Bates, 2006;Ray et al, 2004;Tracy and Bates, 1999), there was a medium effect-size (partial η 2 = .08) interaction between beverage group and emotional cue valence (Figure 2) that did not reach statistical signifi cance. This may suggest that memory priming for emotional cues may be enhanced during acute intoxication; however, studies of larger samples are needed before strong conclusions can be reached.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that alcohol intoxication did not interfere with this mode of implicit memory processing for neutral and emotional picture cues. Although this lack of a main alcohol effect was consistent with the previous literature that used emotionally neutral word cues (Garfi nkel et al, 2006;Lister et al, 1991;Ray and Bates, 2006;Ray et al, 2004;Tracy and Bates, 1999), there was a medium effect-size (partial η 2 = .08) interaction between beverage group and emotional cue valence (Figure 2) that did not reach statistical signifi cance. This may suggest that memory priming for emotional cues may be enhanced during acute intoxication; however, studies of larger samples are needed before strong conclusions can be reached.…”
Section: Discussionsupporting
confidence: 89%
“…These distinct brain and body responses to emotional stimuli result, at least in part, from the plicit memory). A consistent literature documents that, for emotionally neutral cues, acute alcohol intoxication often disrupts intentional, explicit memory while leaving implicit memory intact (Garfi nkel et al, 2006;Lister et al, 1991;Ray and Bates, 2006;Ray et al, 2004;Tracy and Bates, 1999). The current study was designed to examine whether acute alcohol intoxication differentially infl uences memory for emotionally valenced and neutral picture cues using both explicit recall and implicit repetition priming tasks.…”
mentioning
confidence: 97%
“…The task in the current study involved effortful recall of information from long-term memory (e.g., animals at a zoo), and thus our task was more similar to the explicit memory task described above in which alcohol was found to inhibit word recall. Garfinkel et al (2006) studied the effects of alcohol on implicit and explicit false memories. Thirty-two participants consumed a 300 ml drink containing either 0.6 g/kg of alcohol or a placebo.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports in popular news sources of increased rates of injury and alcohol-related illness in young adults after consuming energy drinks containing alcohol (Wake Forest University, 2007). While there is strong evidence that alcohol consumption impairs several aspects of cognition including divided and continuous attention (Fillmore and VogelSprott, 1998;Koelega, 1995;Langer et al, 2005), memory (Garfinkel et al, 2006;Saults et al, 2007;Tracy and Bates, 1999), executive function (Weissenborn and Duka, 2003) and inhibition (Abroms et al, 2006), research on the effects of energy drinks plus alcohol (referred to here as RED þ A) is just beginning to emerge. Ferreira et al (2004) tested the extent to which caffeinated energy drinks mitigated the effects of alcohol during strenuous exercise on a cycle ergometer.…”
Section: Introductionmentioning
confidence: 98%
“…McCloskey & Zaragoza, 1985). And finally, an individual difference that may also affect memory is alcohol consumption, which has shown promise as a factor in other areas of memory distortion research (e.g., Garfinkel, Dienes, & Duka, 2006), but there is a scarcity of data addressing alcohol in crashing memory studies. In the current study, we investigate the role of these variables and others.…”
Section: Previous Crashing Memory Studiesmentioning
confidence: 99%